O espanhol em Sergipe : políticas declaradas, praticadas e percebidas - Loureiro, Valéria Jane Siqueira (2019)
In Brazil, the inclusion of a Foreign Language (FL) teaching offer in the school system was given by Law 9,394 / 96 as a result of a language policy. From 2009, the National High School Examination (ENEM) becomes the main meaning of access to higher education and Spanish, as well as English, became one of the options for choosing the modern foreign language in the exam of Languages, Codes and their Technologies. In the following year, Spanish became a compulsory curriculum content for High School throughout the country as determined by Law 11.161 / 05. In this educational scenario, this paper describes the course of Spanish in the state of Sergipe from the perspective of declared, practiced and perceived language policies (SPOLSKY, 2004, 2009), since the promulgation of Law 11.161 / 05 until 2017, when it was repealed by Law 13.415, which establishes the compulsory English language for elementary school from the sixth grade (year) and all the three years (grades) of high school. Regarding the stated policies in relation to Spanish in Sergipe, the practiced policy was the compulsory plurilingualism, with Spanish sharing space in the curriculum with English, since the State Board of Education, through Normative Resolution 003 of December 22, 2009, established its offer and compulsory enrollment in the public school system, hindering the freedom of choice provided by Laws 9,394 / 96 and 11,161 / 05. Despite the mandatory offer and registration in Sergipe, the language implementation was not homogeneous: Conventional High School state schools allocated the same class time for each of the languages, while state High Schools decided to innovate with the schools allocating twice the class time for the English language. In the conventional high school of the federal network in Sergipe, Spanish was compulsory, and the offer of the other languages, such as English and French, were with optional registration for the students. From the perspective of perceived policies, and considering the leading role of ENEM in the Brazilian educational system, we found that, in 2016, Spanish was the most chosen language in four of the five regions of Brazil. The exception was Southeast, where the percentage of language choice was equal to (50% for each). In the Northeast region (where the state of Sergipe is located, focus of our work/ research), the Spanish corresponded to the choice of 71% of the participants, according to INEP report. In principle, the tendency to choose Spanish could be associated with the result of the stated and practiced policy. This was not what we found in an exploratory investigation into the students' motivations for choosing a foreign language in ENEM 2016, based on the application of a research instrument, in a voluntary sample for adherence of the students of the third year from in four educational institutions of Sergipe (n = 767), classified according to the type of high school offered and network, and linked at the time to the project “Development of social technologies for the formalization and reframing of cultural practices in Aracaju / SE”: Atheneu Sergipense State School (n = 254 ), Professor João Costa State School (n = 364), Minister Petrônio Portela State School (n = 88) and Application School at the Federal University of Sergipe (n = 66). The choice of Spanish was 70%, reflecting the result obtained by INEP. In unveiling the results, we consider that the motivations for learning a foreign language are revealed by curricular normalization (DÖRNYEI, 2001; GARDNER, 1985, 1988), in terms of experiential practices and student engagement. Regarding curriculum normalization, we found that, regardless of the longer exposure to English and the relative superiority of the workload attributed to this language in schools, Spanish was the most chosen language by students in ENEM, which points to the non-effect of politics itself. Regarding experiential practices, the contact that students had outside the school environment was greater with the English language than with the Spanish language. However, even so, Spanish was the most chosen language. As for engagement, students had chosen Spanish justifying their easier comprehension and understanding of this language (CELADA, 2002; KULIKOWSKI; GONZALEZ, 1999); This was, however, the same justification given by those students, who had chosen English. The ease argument does not explain by choice itself; however, we found that those students who had chosen English attributed positive values to this language and negative values to Spanish; the students who had chosen Spanish attributed positive values to both languages. Thus, the choice is much more of positive attitudes result attributed to the language than the obligation and the offer. Law 11.161 / 05 acted positively, as it made compulsory the offer of teaching a foreign language that appears as an option in ENEM, giving the student the opportunity to study a modern foreign language than the hegemonic English language (CANAGARAJAH, 1999). In the field of policies, our study showed that Spanish was, in fact, implemented in public schools in Sergipe. The perceived policies point to the fact that, although this language is the most chosen option in the ENEM evaluation, to access the higher education, it did not occupy a stable prominent role in basic education (BARROS; COSTA; GALVÃO, 2016), despite the stated and practiced policies have paved the way for a possibility of leading Spanish in the brazilian educational system.